Hippocampal CaMKII Regulates the Consolidation of Recognition Memory - Rossato, Janine I.; Gonzalez, Maria Carolina; Apolinário, Gênedy; Radiske, Andressa; Brisa, Elis; Carneiro, Livia Maria; Cammarota, Martín (The European journal of neuroscience, 2025)
ABSTRACT Object recognition memory (ORM) is a hippocampus‐dependent form of memory essential for distinguishing items and constructing episodic representations of the past. Ca2+/calmodulin‐dependent protein kinase II (CaMKII) is a serine/threonine‐specific protein kinase highly enriched in the hippocampal formation, where it acts as a memory‐relevant calcium effector. We found that, in rats, training in an ORM inducing learning task rapidly increased CaMKII autophosphorylation in the CA1 region of the dorsal hippocampus. Moreover, early post‐acquisition intra‐dorsal CA1 injection of the substrate‐competitive CaMKII inhibitor AIP impaired long‐term ORM without affecting short‐term ORM or previously consolidated ORMs. The amnesia induced by AIP was replicated by the calmodulin‐competitive CaMKII inhibitor KN93, but not by the inactive analogues of either KN93 or AIP. Notably, these effects occurred regardless of the subject's sex and age or the time of day when learning took place. Together, our findings indicate that hippocampal CaMKII activity is necessary shortly after training for the normal consolidation of ORM. We show that post‐training inhibition of hippocampal CaMKII in rats, using either autocamtide‐2‐related inhibitory peptide (AIP) or KN93, impairs the consolidation of long‐term object recognition memory (ORM), without affecting short‐term ORM or previously consolidated ORMs. Notably, the amnesic effect of CaMKII inhibition is independent of the rat's sex, age and the time of day at which learning occurs, and is observed only with the active compounds, not their inactive analogues.